Usage of call graph for representing software component interactions - Hashim, Nor Laily; Ismail, Noraini (2012)
A call graph is a ubiquitous representation in most aspect in software engineering. This paper presents an initial proposed technique to represent components relationships in the form of a call graph.To support this study, this paper will cover types of component,a technique used to extract information of component integration,and a process of constructing a call graph, in order to represents the relationship of the component in the software.